2002
DOI: 10.1074/jbc.m207494200
|View full text |Cite
|
Sign up to set email alerts
|

The Cleavage of the Urokinase Receptor Regulates Its Multiple Functions

Abstract: The urokinase-type plasminogen activator (uPA) is able to cleave its cell surface receptor (uPAR) anchored to the cell membrane through a glycophosphatidylinositol tail. The cleavage leads to the formation of cell surface truncated forms, devoid of the N-terminal domain 1 (D1) and unmasks or disrupts, depending on the cleavage site, a sequence in the D1-D2 linker region (residues 88 -92), which in the soluble form is a potent chemoattractant for monocyte-like cells. To investigate the possible role(s) of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(176 citation statements)
references
References 43 publications
8
164
4
Order By: Relevance
“…2A). A likely possibility is that pER-ERY-NH 2 recognizes FPR which is constitutively expressed by HEK-293 cells [14]. To study the role of FPR, we took advantage of RBL-2H3 cells which are devoid of FPR and RBL-2H3/ETFR which stably express FPR [16].…”
Section: Perery-nh 2 Antagonizes Fpr Signallingmentioning
confidence: 99%
“…2A). A likely possibility is that pER-ERY-NH 2 recognizes FPR which is constitutively expressed by HEK-293 cells [14]. To study the role of FPR, we took advantage of RBL-2H3 cells which are devoid of FPR and RBL-2H3/ETFR which stably express FPR [16].…”
Section: Perery-nh 2 Antagonizes Fpr Signallingmentioning
confidence: 99%
“…Furthermore, uPAR can be cleaved by uPA (Hoyer-Hansen et al, 1992) or MMPs in vitro (Andolfo et al, 2002;Koolwijk et al, 2001) and the cleaved uPAR form is also found in invasive tumor xenografts (Solberg et al, 1994). The cleavage occurs between domains 1 and 2 impairs uPA and integrin binding (Montuori et al, 2002) and exposes a chemotactic epitope (Fazioli et al, 1997) suggesting that this cleavage is one of the cell migration regulating events on the cell surface.…”
Section: Other Proteases In Cell Migration and Invasionmentioning
confidence: 99%
“…Only a few other proteins have been shown to directly participate in cell detachment, namely tenascin-C, thrombospondin-1 and -2 and SPARC (secreted protein, acidic and rich in cysteine) (Murphy-Ullrich, 2001). The proteases can also indirectly modulate the affinity and hence the detachment of the cells by processing the extracellular matrix (Giannelli et al, 1997) or by cleaving integrin associated molecules (Andolfo et al, 2002;Montuori et al, 2002).…”
Section: Regulation Of Cell Migrationmentioning
confidence: 99%
“…The membrane was blocked with 5% nonfat dry milk and probed with 1 g/ml of an anti-uPAR polyclonal Ab. Finally, washed filters were incubated with HRP-conjugated anti-rabbit Ab and detected by ECL (10).…”
Section: Western Blotmentioning
confidence: 99%
“…Therefore, uPAR can exist on the cell surface in either a three-domain form (D1D2D3), which is capable of binding uPA, or a two-domain form (D2D3), which does not bind uPA (5). Despite the lack of a transducing cytoplasmic tail, the uPA receptor is able to activate cell signaling pathways, probably by interacting with other cell surface proteins, such as integrins (7,8) and FMLP receptors (9,10), that interact with the cell interior (11).…”
mentioning
confidence: 99%